An Equipment-Free, Paper-Based Electrochemical Sensor for Visual Monitoring of Glucose Levels in Urine. (October 2019) - Mohammadifar, Maedeh; Tahernia, Mehdi; Choi, Seokheun
A novel electrochemical glucose sensor was created for a simple but semiquantitative visual screening of specific glucose concentrations in urine. This noninvasive glucose biosensor integrated a disposable, paper-based sensing strip and a simple amplifier circuit with a visual readout. The paper strip consisted of five enzyme-activated electrodes. Each electrode was connected to a specific indicator circuit that triggered a light-emitting diode (LED) when a predefined glucose concentration was reached. The device features (1) low-cost, disposable, paper-based glucose oxidase (GOx)/poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) sensing electrodes, (2) simple signal amplification, and (3) on-site, rapid, and visual detection. The sensor generated reliable, discrete visual responses to determine five glucose levels (1, 2, 3, 4, and higher than 4 mM) in urine in less than 2 min. This innovative approach will provide a simple but powerful glucose sensing paradigm for use in POC diagnostics.